Peran Guru Dalam Pengembangan Peserta Didik di Era Digital - Tari, Ezra; Hutapea, Rinto Hasiholan (Kharisma: Jurnal Ilmiah Teologi, 2020)
The author examines the development of students in the digital age.  This study departs from the writer's anxiety about the condition of students in the digital age.  The students have not been able to use technology maximally. So that teachers are required to act professionally to assist students to develop themselves in the mastery of information technology. On account of these problems, the authors explore the role of teachers in the development of students in the digital age.  The method used is descriptive qualitative.  In this study, the theory used in research is not forced to obtain a complete picture of a matter according to human views. Based on the study conducted by the author in this paper, the ability to manage learners, teachers are responsible for students in the design and implementation of learning outcomes. Development of students, with a number of roles and responsibilities undertaken by the teacher. So the teacher must be proficient, clever, careful, and smart in carrying out work as a teacher.  Teachers are required to be able to actualize pedagogical competencies and able to implement holistic education.Penulis mengkaji tentang pengembangan peserta didik di era digital. Penelitian ini berangkat dari keresahan penulis terhadap keadaan peserta didik di era digital.Para peserta didik belum mampu menggunakan teknologi secara maksimal. Sehingga guru dituntut untuk bertindak profesional untuk mendampingi nara didik untuk mengembangkan diri dalam penguasaan teknologi informasi. Dengan problematika tersebut maka, penulis mengupas tentang peran guru dalam pengembangan peserta didik di era digital. Metode yang digunakan adalah kualitatif deskriptif. Dalam penelitian ini, teori yang digunakan dalam penelitian tidak dipaksakan untuk memperoleh gambaran seutuhnya mengenai suatu hal menurut pandangan manusia. Berdasarkan kajian yang dilakukan oleh penulis dalam tulisan ini, kemampuan pengelolaan peserta didik, guru bertanggungjawabterhadap peserta didik dalam perancangan dan pelaksanaan hasil belajar.Pengembangan peserta didik, dengan sejumlah peran dan tanggung jawab yang dilakukan guru. Jadi guru wajib mahir, pandai, cermat, dan cerdas dalam menjalankan pekerjaan sebagai guru. Guru dituntut mampu mengaktualisasikan kompetensi pedagogik. Serta mampu mengimplementasikan pendidikan yang holistik.